O synonimii pojęć przyjąć - odebrać w socjolekcie siatkarskim - Kochmańska, Wioletta (Słowo. Studia językoznawcze, 2013)
The author of the paper proves the synonymy existence of the verbs accept – receive in a volleyball sociolect and explains the identity mechanism of the verbs meaning. The stages of the scientific research include: the analysis of the meaning attributed in lexicographical sources and a cultural stereotype, a linguistic picture reproduction of a contextual confrontation accept – receive a serve and a usage presentation of both verbs in sports coverage.